2023
DOI: 10.1021/acs.accounts.3c00145
|View full text |Cite
|
Sign up to set email alerts
|

Reticular Electrochemiluminescence Nanoemitters: Structural Design and Enhancement Mechanism

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Electrochemiluminescence (ECL) is a powerful transduction technique, which depends critically on the formation of the excited emitter through the charge transfer between the electrochemical reaction intermediates of the emitter and the co-reactant/emitter. The exploration of ECL mechanisms for conventional nanoemitters is limited due to the uncontrollable charge transfer process. With the development of molecular nanocrystals, reticular structures such as metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The reduction potential of TPP is in the range of −1.0 to −1.2 V. In contrast, C X produces a new reduction peak in the range of −0.2 to −0.4 V, which is due to the reduction of the cationic pyridinium moiety as reported . As shown in Figure C, the reduction peak at −0.83 V was observed for K 2 S 2 O 8 solution, indicating the formation of SO 4 •– . The TPP-modified electrode presents an irreversible reduction peak at −1.15 V ascribing to the electrochemical reduction of TPP and the reaction between S 2 O 8 2– and TPP anions .…”
Section: Methodssupporting
confidence: 54%
“…The reduction potential of TPP is in the range of −1.0 to −1.2 V. In contrast, C X produces a new reduction peak in the range of −0.2 to −0.4 V, which is due to the reduction of the cationic pyridinium moiety as reported . As shown in Figure C, the reduction peak at −0.83 V was observed for K 2 S 2 O 8 solution, indicating the formation of SO 4 •– . The TPP-modified electrode presents an irreversible reduction peak at −1.15 V ascribing to the electrochemical reduction of TPP and the reaction between S 2 O 8 2– and TPP anions .…”
Section: Methodssupporting
confidence: 54%
“…Metal–organic frameworks (MOFs), as exemplary inorganic–organic hybrid materials, have attracted considerable attention for electrochemiluminescence (ECL) sensing due to their remarkable features such as high porosity, exceptional surface area, and customizable chemical structures. , Notably, self-luminescent MOFs with ECL activity have garnered significant interest in the field of biosensing. Previous studies have demonstrated the development of ECL emitters using Ru­(bpy) 3 2+ derivatives/porphyrin-based MOFs for the construction of biosensors capable of selective multiple-target analysis. However, the presence of aggregation-caused quenching remains a challenge due to the agglomeration tendencies of the Ru (II) complex or porphyrin molecules, thereby limiting the ECL efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Following up this way of reformulation, an advanced plan is to condense both luminophores and their coreacting chaperones in a more orchestrated formalism, which might hopefully got realized with the burgeoning nanoreticulation . Presumably, the stochastic unimolecular redox in any ECL elementary reaction as the Bulter–Volmer equation described would turn to happen in a framework-rectified dielectric layer, thus securing a statistically much evener and denser radiation flux.…”
Section: Introductionmentioning
confidence: 99%